Interatomic decay of inner-valence ionized states in ArXe clusters: Relativistic approach - Faßhauer, Elke; Pernpointner, Markus; Gokhberg, Kirill (The journal of chemical physics, 2013)
In this work we investigate interatomic electronic decay processes taking place in mixed argon-xenon clusters upon the inner-valence ionization of an argon center. We demonstrate that both interatomic Coulombic decay and electron-transfer mediated decay (ETMD) are important in larger rare gas clusters as opposed to dimers. Calculated secondary electron spectra are shown to depend strongly on the spin-orbit coupling in the final states of the decay as well as the presence of polarizable environment. It follows from our calculations that ETMD is a pure interface process taking place between the argon-xenon layers. The interplay of all these effects is investigated in order to arrive at a suitable physical model for the decay of inner-valence vacancies taking place in mixed ArXe clusters.